2017
DOI: 10.3892/ijmm.2017.3291
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin prevents high-fat diet-induced rat non-alcoholic fatty liver disease through the AMPK and LXR signaling pathways

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a major public health concern worldwide. The aim of the present study was to observe the effect of diosgenin on NAFLD and investigate the underlying mechanisms. Diosgenin treatment increased the phosphorylation of AMP-activated protein kinase (AMPK) and acetyl-CoA carboxylase (ACC) in HepG2 cells. Diosgenin significantly inhibited high glucose (HG)-induced triglyceride (TG) accumulation and sterol regulatory element‑binding protein-1c (SREBP-1c) mRNA increase in Hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 33 publications
4
33
0
Order By: Relevance
“…Our results showed that ALM16 reversed the HFD-induced downregulation of CPT-1, involved in fatty acid oxidation, in the HFD-fed mice. Similarly, several studies have reported that the protective effects against hepatic steatosis are mediated by the downregulation of genes involved in lipogenesis and upregulation genes associated with fatty acid oxidation via enhanced AMPK signaling [60,61]. e results showed that AM treatment alone downregulated the FAS protein expression by activating AMPK phosphorylation, while it had no effect on the SREBP-1c and CPT-1 expressions.…”
Section: Discussionmentioning
confidence: 81%
“…Our results showed that ALM16 reversed the HFD-induced downregulation of CPT-1, involved in fatty acid oxidation, in the HFD-fed mice. Similarly, several studies have reported that the protective effects against hepatic steatosis are mediated by the downregulation of genes involved in lipogenesis and upregulation genes associated with fatty acid oxidation via enhanced AMPK signaling [60,61]. e results showed that AM treatment alone downregulated the FAS protein expression by activating AMPK phosphorylation, while it had no effect on the SREBP-1c and CPT-1 expressions.…”
Section: Discussionmentioning
confidence: 81%
“…Although HepG2 cells originate from hepatoblastoma ( 16 ), the study by Gómez-Lechón et al ( 17 ) demonstrated that fat overaccumulation is induced in hepatic cells by FFA, and that human hepatocytes and HepG2 cells behave nearly the same. HepG2 cells are, therefore, generally accepted as a promising alternative to human hepatocytes for use as a cellular model of steatosis ( 17 19 ). HepG2 cells were cultured in Dulbecco's modified Eagle's medium (DMEM; Gibco; Thermo Fisher Scientific, Inc., Waltham, MA, USA) supplemented with 10% fetal bovine serum (FBS; Gibco; Thermo Fisher Scientific, Inc.) and 1% penicillin/streptomycin at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…This finding corroborates the observation that diosgenin increases levels of antioxidant and hepatoprotective enzymes in the blood plasma and liver, with concomitant improvement of β-cell regeneration and insulin secretion in streptozotocin-induced diabetic rats [ 40 ]. It has been also found that diosgenin increases the phosphorylation of AMP-activated protein kinase (AMPK) and acetyl-CoA carboxylase (ACC) in HepG2 cells, furthermore it suppresses LXRa in a rat model of non-alcoholic fatty liver disease (NAFLD), thus preventing development of NAFLD [ 48 ].…”
Section: Discussionmentioning
confidence: 99%